2002
DOI: 10.1021/ac020517o
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Detection of Unstained Proteins in Acrylamide Gels by Native UV Fluorescence

Abstract: Visualization of proteins inside acrylamide and other gels usually relies on different staining methods. To omit the protein-staining procedure, we visualized unstained proteins inside acrylamide gels by laser excitation with ultraviolet (UV) light (280 nm, 35 mJ/cm 2 ) and directly detected native UV fluorescence. In one-dimensional gels, a detection limit as low as 1 ng for bovine serum albumin and 5 ng for other proteins with a linear dynamic range (2.7 orders of magnitude) comparable to state of the art fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 20 publications
0
49
0
Order By: Relevance
“…8, methylation of both the 1716 Da and 1196 Da peaks was evident in the peak list and spectrum of the CBB G-250 stained apolipoprotein c-III. Recently a stainfree fluorescent technique has been developed for imaging spots in polyacrylamide gels [28]. Unfortunately, the technique was less sensitive than silver with a detection limit of around 5 ng per band for four proteins in 1-D gels.…”
Section: Discussionmentioning
confidence: 99%
“…8, methylation of both the 1716 Da and 1196 Da peaks was evident in the peak list and spectrum of the CBB G-250 stained apolipoprotein c-III. Recently a stainfree fluorescent technique has been developed for imaging spots in polyacrylamide gels [28]. Unfortunately, the technique was less sensitive than silver with a detection limit of around 5 ng per band for four proteins in 1-D gels.…”
Section: Discussionmentioning
confidence: 99%
“…The LLD of PhosB, CA and glyceraldehyde 3-phosphate dehydrogenase was 5 ng and 1 ng for BSA. The LDR was between 1 and 500 ng of protein and 2D analysis of EA.hy 926 soluble proteins showed that native fluores-cence detected 86% of spots relative to silver staining [194]. This procedure for in-gel protein detection is, however, very lengthy and requires up to two weeks for completion.…”
Section: Additional Fluorescent Stainsmentioning
confidence: 98%
“…Since the introduction of native protein detection in gels, there have been various attempts to capitalize on and improve this process [185,[191][192][193]. Native fluorescence has demonstrated protein detection comparable to that achieved with silver staining [194]. The LLD of PhosB, CA and glyceraldehyde 3-phosphate dehydrogenase was 5 ng and 1 ng for BSA.…”
Section: Additional Fluorescent Stainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with thrombospondin they constitute the predominant majority of the total protein amount in platelets, representing the major drawback of complex analyses because all separation and identification techniques are restricted with regard to dynamic range. Protein staining methods have a dynamic range between ϳ50 for Coomassie Brilliant Blue TM , 1,000 for silver staining procedures, and up to 10,000 for fluorescent dyes (13,14). In correlation, chromatographic separation is limited in binding capacity and dynamic range, too.…”
mentioning
confidence: 99%